Role of the Orexin System on the Hypothalamus-Pituitary-Thyroid Axis - Messina, Antonietta; De Fusco, Carolina; Monda, Vincenzo; Esposito, Maria; Moscatelli, Fiorenzo; Valenzano, Anna; Carotenuto, Marco; Viggiano, Emanuela; Chieffi, Sergio; De Luca, Vincenzo; Cibelli, Giuseppe; Monda, Marcellino; et al. (Frontiers in Neural Circuits, 2016)
Hypocretin/orexin are two hypothalamic neuropeptides discovered in 1998. Since their discovery, they had been one of the most studied neuropeptide systems because of their projecting fields innervating various brain areas. The orexinergic system is tiedto sleep-wakefulness cycle, and narcolepsy is a consequence of their system hypofunction. Orexinergic system is also involved in many other autonomic functions such as feeding, thermoregulation, cardiovascular and neuroendocrine regulation. The main aim of this mini reviewis to investigate the relationship between orexin and thyroid system regulation. Although knowledge about the orexin system is evolving, its putative effects on Hypothalamic-pituitary-thyroid (HTP) axis still appear unclear. We analyzed some studies about orexin control of HTP axis to better know the relationship between them. The studies we analyzed suggest an action of the Hypocretin/orexin tomodulate the thyroid regulation but the nature (excitatory or inhibitory) of this possible interaction remain actually unclear and it need to be confirmed.